PERKEMBANGAN EKSPOR LAMPIT ROTAN DI PROPINSI KALIMANTAN SELATAN - Setiasih Irawanti (Jurnal Penelitian Hasil Hutan, 1990)
Floor mats iB  the main export commodity    from South  Kalimantan Province. The decrease of floor mats export demand from  thiB province since  the end of  1988  indicates the beginning of busine•  slow down period of (loo'lt.. mats.The study results using multiple regreBBion analysiB, showed that among four variablesi.e. yen exchange rute against the US dollar (X1),  interest rate in ~apan (Xa),  t. he Indonesian government po_l~  to su11_port e~port of (iniBhed products nattan (Xa)  ai1d  change of season in Japan (X4), ,only two variablesgave a szgnlficant impact on the floor mats esport volume (denoted by Y). These two variablesare the yen exchange rate against US dollar (X 1) and the season (X4'.  The relationship can be expreued  by a multiple regresion equation as follows : In  Y  -  21.4608-3.0463   In x1-o.6206   In x2+0.2744 x3+0.7537 X4+E  with  the coefficient of  determination (R2)  of  0,6367.